Increased waist circumference as an independent predictor of hypercholesterolemia in community-dwelling older people - Claudineia Matos de Araujo; Marcos Henrique Fernandes; José Ailton Oliveira Carneiro; Raildo da Silva Coqueiro; Rafael Pereira (PAGEPress Publications, 2018)
Hypercholesterolemia is a worldwide public health problem, contributing to cerebrovascular and ischemic heart diseases as one of the major cardiovascular risk factors, and associated with approximately 4.4 million deaths each year worldwide. This study aimed to evaluate the association and predictive value of increased waist circumference (WC) to identify hypercholesterolemia in community-dwelling elderly people. In a cross-sectional, homebased epidemiological survey, 296 community-dwelling old adults consented to capillary blood collection and anthropometric evaluation. Total cholesterol was quantified, and the population was stratified as normal or high (≥200 mg/dL). WC was used to stratify the population into normal or elevated values (men: ≥90 cm; women: ≥80 cm). The association was investigated using logistic regression. Increased WC was associated with a greater probability of hypercholesterolemia (OR=2.82, 95%CI 1.68 to 4.74). Thus, the widely used WC cutoff was demonstrated to be significantly associated with hypercholesterolemia in community-dwelling elderly people and could serve as a useful screening tool for hypercholesterolemia in older adults.